Nudging sustainability transitions in Central Mozambique - Homann-Kee Tui, Sabine; Falk, Thomas; Sixpence, C.; Gungulo, A.; Quembo, C. (2019)
An Agricultural Innovation Platform (AIP) facilitates and accelerates transition of farmers from subsistence farming to socially inclusive, environmentally sound and market-oriented farming. AIPs adapt interventions around interlinked levers in the food value chains, with entry points based on a good understanding of farming systems and input/output market requirements. Learning activities around these entry points strengthen stakeholder networks. Capacitating farmers through stakeholder networks, using mutual learning and additional technical training sessions, improves their self-organization and helps them become entrepreneurs, with the private sector as business mentors and government and extension as facilitators and support. Prospects for change in complex farming systems often appear few and uncertain, leaving farmers feeling helpless in the face of challenges. AIPs demonstrate that small interventions around significant leverage points will have far-reaching benefits. With time, stakeholders facilitate multiple changes through AIPs, magnifying the impact and paving the way for initiatives beyond a project’s lifespan. The ‘AIP experience’ changes their self-perception, resilience, motivation and empowerment forever.